Information technologies and key components for ensuring patient safety in anesthesiology and intensive care units with different levels of digitalization (message 3) - V. I. Gorban (Вестник анестезиологии и реаниматологии)
The objective was to assess the relationship between the implementation of information technologies in the work of anesthesiology and intensive care services of multidisciplinary hospitals and the severity of the leading components of patient safety at different levels of digitalization.Materials and methods. Expert assessment of the level of digitalization and the effectiveness of using new medical information technologies in the system of the anesthesiology and intensive care service (department) of 235 multidisciplinary hospitals, including an assessment of the leading components of patient safety at different levels of digitalization. Statistical analysis of data distribution, Student’s t-test for independent samples.Result. It has been established that the majority (47.7%) of anesthesiology and intensive care units (AICU) of multidisciplinary hospitals in the Russian Federation are at the average (sufficient) level of digitalization. Relatively few (19.2%) AICU of multidisciplinary hospitals are at a high and sufficiently high level in terms of digitalization. At the same time, each of the levels of digitalization of the AICU of multidisciplinary hospitals has a close relationship with the severity of the main components of ensuring the safety of patients in the departments.Conclusion. Comparison (correlation) of the level of digitalization and components of patient safety of the AICU of multidisciplinary hospitals showed their fairly close and direct relationship. The study confirms that the effectiveness of ensuring patient safety of the AICU of multidisciplinary hospitals is associated, first of all, with a high level of digitalization as an important integral process for ensuring the quality of specialized medical care.